Arduino Smart Parking Manage System based on Ultrasonic Internet of Things (IoT) Technologies - Hassan Kadhim, Maher (International Journal of Engineering and Technology, 2018)
Nowadays, the Internet of things (IoT) plays an important role in our life by connecting things with humans via the internet. This study proposes a smart system based on Arduino components, website and mobile application. The system helps drivers to find an empty park space depending on the number of unoccupied lots in the park. The parking lots are impossible to be reserved with the ordinary parking system. This study provides a mobile app that can be utilized to find a free lot in a nearest park. Smart parking can increase the economy by reducing fuel consumption and pollution in urban cities. Moreover, it helps to reduce the time of finding car lot. Also, it helps the driver to find his car when he forgets the car location easily. However; the system adopts new tablesâ€™ structure, yellow booking light in the parking lot, books and buys through app and gate monitor. Finally, the system shows the reserved, booked and empty lots in park for staff and drivers.Â Â